Creación De Una Unidad Documental De La Universidad Estatal De Bolívar, Facultad De Ciencias De La Educación, Sociales, Filosóficas Y Humanísticas, Sistema De Educacion Semipresencial, Año 2009 - Paredes Paredes, Edmundo Raúl (2011)
This paper, "Creating a Documentary Unit Bolívar State University Faculty of Education, Social, Philosophical and Humanities, Education System Blended, 2009 forms with other works of the same features, of a whole Documentary Unit is serving the felt need to organize and systematize undergraduate thesis and related Carreras and the various faculties of the State University of Bolivar, in order to use that must give students, teachers and researchers. For this purpose, specifically it entered information in the SIABUC program using the MARC format, by prior application of technical processes of classification, coding, cataloging and indexing. This database is the final destination, the online consultation by internal and external users. The realization of this project also looked at the proposed creation of a documentation unit, where it is administered, managed and bid broadcasting services, promotion and consultation of the scientific production of Bolívar State University.